Impact of demographic factors on chronic pain among adults in the United States - Peter M. Mullins; Robert J. Yong; Neil Bhattacharyya (PAIN Reports, 2022)
Abstract. Introduction:. Chronic pain affects more than 1 in 5 American adults, and its effects are not evenly distributed throughout the population. Methods:. Using the National Health Interview Survey (NHIS), a household-based annual survey of self-reported health status of U.S. adults, this cross-sectional study describes differences in the prevalence of chronic pain and its effects across socioeconomic groups. Results:. In univariate analyses, chronic pain was more prevalent among female respondents, persons with lower educational attainment, non-Hispanic White individuals, and those who were insured as well as those who were married. After accounting for all other demographic factors, age, female sex, and lower educational attainment were associated with higher odds of having chronic pain, whereas Hispanic and non-Hispanic Black race were associated with lower odds. Despite lower odds of having chronic pain, Hispanic and non-Hispanic Black race were associated with greater odds of reporting more severe pain than White race. There were no significant differences across race in the effects of pain on life, work, or family, although female sex and lower educational attainment were associated with greater effects of pain on these domains. Educational attainment was the only characteristic associated with greater odds of ineffective pain management after accounting for all other demographic factors. Conclusions:. Implications for reducing disparities in the treatment of chronic pain are discussed.